2021
DOI: 10.1002/rcm.9157
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of metabolic fate of phellodendrine and its potential pharmacological mechanism against diabetes mellitus by ultra‐high‐performance liquid chromatography‐coupled time‐of‐flight mass spectrometry and network pharmacology

Abstract: Rationale Characterizing the functional mechanism of quality control marker (Q‐marker) was of great importance in revealing the primary pharmacological mechanism of herbs or the other complex system, and drug‐related metabolites always contribute to the pharmacological functions. Cortex Phellodendri was used as a core herb in the treatment of diabetes mellitus (DM). As a Q‐marker of Cortex Phellodendri, the role of phellodendrine in DM was still unclear. Thus, the characterization of phellodendrine‐related met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…If metabolites have potential biological activities, they should be included with prototype compounds in the network pharmacology analysis. Zhang et al [25] used phellodendrine and its main in vivo metabolites to explore the potential pharmacological network to address diabetes mellitus. Arctiin and prim- O -glucosylcimifugin and their in vivo metabolites were used for network pharmacology analysis [26] , [27] .…”
Section: Network Pharmacology For Chm Researchmentioning
confidence: 99%
“…If metabolites have potential biological activities, they should be included with prototype compounds in the network pharmacology analysis. Zhang et al [25] used phellodendrine and its main in vivo metabolites to explore the potential pharmacological network to address diabetes mellitus. Arctiin and prim- O -glucosylcimifugin and their in vivo metabolites were used for network pharmacology analysis [26] , [27] .…”
Section: Network Pharmacology For Chm Researchmentioning
confidence: 99%
“…Phellodendrine shows protective activity against AAPH-induced oxidative stress, which is similar to the inflammatory response in vivo ( Li et al, 2016 ). Previous network pharmacology research has demonstrated that phellodendrine can be used against diabetes mellitus through the calcium signaling pathway, cGMP-PKG signaling pathway, and cAMP signaling pathway ( Zhang et al, 2021 ). Phellodendrine may inhibit the proliferation or the migration of macrophages and cytotoxic T lymphocytes in the glomeruli, showing high effectivity in anti-GBM nephritis ( Hattori et al, 1992 ).…”
Section: Introductionmentioning
confidence: 99%